Analysis of A Business Feasibility Study Using A Business Model Canvas For The Establishment of A Subsidiary in the Training Provider Field - Ahmad Mukhibbin; Marni Astuti; Eko Poerwanto (SENATIK STT Adisutjipto, 2019)
PT. XYZ is a company engaged in aircraft MRO (Maintenance, Repair and Repair) services by providing integrated solutions for all of its customers. Unit Learning Services at PT. XYZ has the task of organizing education and training. In accordance with the plan of PT. XYZ, Learning Services Unit is focused on preparing to spin off to become a subsidiary engaged in the Provider of Training. This study aims to determine what kind of subsidiary business model will be created using the canvas business model and conduct a business feasibility study, whether it is feasible or not. The results of this study are based on the canvas business model which has the following proposition values: (1) Highly qualified instructors with years of experience in aircraft maintenance; (2) Aircraft access for training; (3) Spacious classrooms including ACT instructors for Airbus qualified training classes; (4) Adjustable training for customer needs; and based on aspects that are processed for the establishment of a subsidiary is declared feasible.